(untitled) (LEARNing Landscapes, 2015)
The purpose of this article is to describe a professional development program for principals focused on their engagement in action research, the systematic and intentional study by principals of their own administrative practice. The program is described in detail along with a brief analysis of the action research produced by the principals, a report of the principals’ perceptions of the action research experience from survey data, and the authors’ reflections on important considerations to take into account when designing a long-term program of principal professional development that endeavors to develop principals as action researchers.